Design and Implementation of PID and Fuzzy-PID Controllers for Ball-on-Plate - Quoc-Khanh Tran; Pham-Minh-Trong Vo; Hoang-Dung Nguyen; Tran-Nhat Dang; Thi-Ngoc-Thao Nguyen; Thi-Hong-Lam Le; Phong-Luu Nguyen; Thanh-Binh Nguyen; Van-Hiep Nguyen; Ngoc-Long Le (Journal of Fuzzy Systems and Control, 2026)
This paper presents the design, implementation, and comparative evaluation of a conventional PID controller and a Fuzzy-PID controller for a nonlinear Ball-on-Plate (BoP). The primary objective is to stabilize the ball at a desired position on the plate while achieving a fast transient response and robustness against disturbances. A conventional PID controller is first designed and tuned using the Ziegler–Nichols method. To improve performance under nonlinear conditions, a Fuzzy-PID controller is developed in which fuzzy logic adaptively adjusts the PID gains online. The proposed controllers are evaluated through three stages: numerical simulation in MATLAB/Simulink, real-time implementation in Python, and experimental validation on a physical hardware platform. Compared with the conventional PID controller, the Fuzzy-PID controller achieves a reduction in maximum overshoot from 0.17% to below 0.1% in simulation, a shorter settling time (approximately 4.0 s for PID versus 2.8 s for Fuzzy-PID), and a reduction in steady-state positioning error of approximately 33–36% in hardware experiments (from ~3–14 pixels to ~2–9 pixels).